Study on Polishing Technologies for Additive Manufacturing Parts - Wan Zhiqiang; Patrick Teo Hiu Hong; Go Tze Fong; Walisijiang.Tayier; Hua Xia (Penerbit Universiti Kebangsaan Malaysia, 2025)
Additive manufacturing has a good application prospect in aerospace, medical implantation and other fields, but the molding surface quality is poor, without post processing can not meet the requirements of high service, polishing processing is a key link in the high-performance metal additive manufacturing technology chain. This paper summarizes the characteristics of the ladder effect, the high roughness of the forming surface. In recent years, additive manufacturing technology, also known as 3D printing, has been highly valued by aviation enterprises for its unique advantage in rapid prototyping, particularly for complex metal parts. However, due to the layer-by-layer growing process of 3D printing, the built parts often have poor surface roughness and are not suitable for practical use without post-treatment. Based on this foundation, the primary focus of research in the field of additive manufacturing for metal parts polishing includes electrochemical, laser, and abrasive fl ow polishing technologies. The progress in these areas is examined with consideration given to various manufacturing processes, different types of metal powder materials, and diverse structures (such as porous structure and high aspect fl ow channels) found in additive manufacturing samples. This review summarizes the research findings related to surface roughness, material removal, surface residual stress, profile accuracy retention, and other technical indicators associated with the polishing process for additive manufacturing metal parts. Finally, the paper discusses potential future developments in polishing technology for 3D printed metal parts.